BIOKOMPOS CAIR DAN PUPUK KIMIA NPK SEBAGAI ALTERNATIF NUTRISI PADA BUDIDAYA TANAMAN CAISIM TEKNIK HIDROPONIK - Djamhari, Sudaryanto (Badan Pengkajian dan Penerapan Teknologi, 2012)
Technique hydroponic system with Nutrient Film Technique (NFT), is one way of vegetable crops that can be done in a narrow and without the use of soil media. Nutrition is done by pouring so that it can carry oxygen (O2) from the air. Generally fertilizer nutrient used in hydroponic technique is AB-mix, this study sought to examine alternative combinations of NPK fertilizer and liquid biokompos on some degree of concentration thatcan provide optimum production growth in crop varieties caisim Tosakan. This experiment used Completely Randomized Design (CRD) with 4 treatments. Data analysis was performed using different test each plant and resumed Duncan Multiple Test Distance otherwise known Duncan's Multiple Range Test (DMRT) at 5% level (F count> F table orP> 0.05) was conducted to determine the extent of the effect is real or not experiment treatmentResearch results indicate that administration of a mixture of NPK fertilizer and liquid fertilizer biokompos An1O1 the treatment can be used as a substitute for AB-mix in the provision of nutrition to the cultivation of varieties caisim Tosakan with hydroponictechniques. An1O1 treatment is the best dose when compared to the control treatment AB-mix, An2O2, and An3O3 the highest production yield component (gross production amounted to 97.67 g / plant and 85.75 g CP / tan).